Motifs for Emphasizing Corners in the Characterization of Corner Infill Buildings - Alfirević, Đorđe; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2021)
The subject of the paper is corner infills in the urban environment. The term “corner infill” means an architectural object (house or building) that completes the continuity of two sequences of architectural objects that meet at an angle. One of the most important elements in the articulation of a corner house is the contact zone between the two external facades. Under certain circumstances, the so-called “corner theme” can become their meeting point. The corner theme in architecture implies a place that is emphasized in relation to the adjacent facade planes or the volumetry of the building. Although the principle of corner accentuation in architecture is present in most corner houses, there are numerous examples of urban infills in which the corner is not emphasized. That gives the impression that there are certain motifs or circumstances due to which the corner is accented or unaccented. The focus of the paper is not on the formal aspects of the corner articulation, but on analyzing the causes of the appearance of the corner motif. In the paper, characteristic examples of corner houses are considered through scientific analysis, and then the regularities are explored. The motifs that influence the emphasis of the angle in the interpolated building’s composition were ascertained by the method of generalization. The aim of the research was to re-examine the position according to which the corner theme in urban infills is justified in situations when the house fits into the immediate urban environment of cultural-historical or architectural significance. On the other hand, if the house is connected to surrounding buildings of lower quality or significance, the theme of the corner loses its meaning, because the whole house becomes a new city reference point, therefore emphasizing that the corner is superfluous.